PELAKSANAAN SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM PENGEMBANGAN PROFESIONALITAS GURU - Said Subhan Posangi (RUMAH JURNAL - LP2M IAIN SULTAN AMAI GORONTALO JURUSAN PENDIDIKAN GURU MADRASAH IBTIDAIYAH (PGMI) FAKULTAS ILMU TERBIYAH DAN KEGURUAN, 2021)
ABSTRACT This study aims to see the implementation of the principal’s academic supervision in the development of teacher professionalism. The research method used in this research is descriptive qualitative with data collection techniques by observation, interviews and documentation. The results of the study found that the planning carried out by the principal was well structured in accordance with the existing provisions, as for the academic supervision carried out by the principal, namely, first the principal set goals, the second held discussions with teachers and other personnel by deliberation/meeting, and The third is carrying out the academic supervision schedule which will be carried out in one semester there are 2 times, namely at the beginning of a new teaching and at the end. The educational process in each educational unit is carried out by providing examples, building the will, and developing the creativity and independence of students in accordance with the development, intelligence, and independence in the context of achieving graduate competency standards. In every implementation of a program that has been planned, it must not be separated from the obstacles and difficulties. From this description, the researcher concludes that the implementation of academic supervision is assistance given by the principal to improve the teaching and learning situation, whether success or failure is largely dependent on the supervisor. Professional.